Safety-netting strategies for primary and emergency care: a codesign study with patients, carers and clinicians in Sweden - Sara Riggare; Rita Fernholm; Karin Pukk Härenstam; Carolina Wannheden; Johanna Hagman (BMJ Open, 2024)
Objectives To codesign safety-netting strategies for primary and emergency care settings by integrating the experiences and ideas of patients, carers and clinicians.Design A codesign process involving two focus group discussions, eight individual interviews and five workshops. All sessions were audio recorded and transcribed verbatim. Data were analysed using qualitative content analysis and reported using the Consolidated criteria for Reporting Qualitative research guidelines.Setting Primary and emergency care in Sweden, focusing on the Stockholm region.Participants 7 (5 women) individuals with patient expertise, 1 (man) individual with carer expertise, 18 (12 women) individuals with clinical expertise.Results Three main categories reflecting strategies for applying safety-netting were developed: first, conveying safety-netting advice, which involves understanding patient concerns, tailoring communication and using appropriate modalities for communicating; second, ensuring common understanding, which involves summarising information, asking a teach-back question and anticipating questions post consultation; and third, supporting safety-netting behaviour, which involves facilitating reconsultation, helping patients and carers to navigate the health system and explaining the care context and its purpose.Conclusions Our study highlights the collaborative nature of safety-netting, engaging both the clinician and patient, sometimes supported by carers, in an iterative process. Adding to previous research, our study also emphasises the importance of anticipating postconsultation inquiries and facilitating reconsultation.